PEMANFAATAN LIMBAH KULIT SINGKONG, KULIT PISANG DAN KULIT KENTANG SEBAGAI BAHAN PAKAN TERNAK MELALUI TEKNIK FERMENTASI - Akhadiarto, Sindu (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2009)
Indonesia as an agricultural country have many agriculture waste that usefull for feedingredients, contained high energy but low protein. The constraints from the use of thosefeed ingredients are that they have low nutrient content, low economic value as feed,unavailable continously, hard to handle, need certain facility, need high transportationcost, low storage periode and high toxin contamination. Microbiology can handle thoseconstraints by the use of microbes, which recently used in feed industry. This reseachhave goal for improving protein contain of cassava peel, bananas peel and potatos peelwhich fermented by Aspergillus niger. The methodology done by solid fermentation asORTSOM method and IRCHA method.Cassava peel, bananas peel and potatos peelsterilized by boiling and nitrogen analyzed by Kjeldahl method. The result show thatprotein contains of cassava peel, bananas peel and potatos peel increase significantly.(p<0.05.) and they can be as substrat for Aspergillus niger medium for industry